(untitled) (Journal of Pharmacy and Nutrition Sciences, 2022)
This study aimed to estimate the protective effect of a combination of S-Adenosyl-L-methionine (SAM) as a precursor of glutathione and oseltamivir as a specific inhibitor of virus replication on oxidative damages caused by influenza infection in the liver of infected mice. Albino mice were inoculated with 10×LD50 of influenza virus A/Aichi/2/68(H3N2). Oseltamivir was applied for five days after infection, twice per day, in a dose of 2.5 mg/kg. SAM was applied for ten days in a 100 mg/kg dose, starting five days before inoculation. Markers of oxidative stress, mortality rate, mean survival time, index, and protection coefficient were followed. Influenza infection causes severe oxidative damage to the liver. All combinations of SAM and oseltamivir restored the levels of the biochemical markers to those in healthy animals and improved the virological parameters. A combination of SAM 100 mg/kg and oseltamivir 2.5 mg/kg, which is 1/4 of the optimal therapeutic mice dose, exhibits protection index and affects most effectively all the tested parameters. This study provides an easy-to-apply approach with a good therapeutic potential for co-medicating influenza infection with a specific antiviral agent and an antioxidant precursor.